Estudio morfológico del danzante de Pujilí realizado a un grupo de niños de la parroquia La Victoria para impulsar la identidad de Cotopaxi - Arcos Cuyachamín, Melanie Estefania (2023)
The new generations are leaving aside their culture to adapt to new trends, however, the scarce cultural education in native infants of the La Victoria parish has been evidenced, in which its traditional festival "Corpus Christi" is nationally and internationally known. made up of several characters, the main one is the Dancer of Pujilí, whose origin dates back about 70 years. This symbolic character is the central figure of this festivity, his attractive and striking dance captivates the spectators. This investigative study aims to enrich the cultural value of the La Victoria parish, especially the students of the Educational Unit October 14 "Vicente Rocafuerte". As well as encourage children to appreciate the importance of this fundamental character through a workshop.